Analysis of the competitiveness of small, medium, and large sugarcane producers: A study among suppliers in the state of São Paulo, Brazil - de Amorim, Fernando Rodrigues [UNESP]; Guimarães, Camila Carla; Queiroz, Timóteo Ramos [UNESP]; Batalha, Mário Otávio (My University, 2023)
Over the past few years, the Brazilian sugar-energy sector has sought strategies to remain highly competitive in the production of sugar and ethanol from sugarcane. Some studies reveal that the competitiveness of the sugar and alcohol industry is conditioned by the productivity of the sugarcane raw material, which in turn seem to be linked to the production scale. The different realities of sugarcane suppliers make it difficult to analyze and, consequently, to adopt measures that increase the competitiveness of the sector. In this sense, the objective of this study was to carry out a descriptive analysis of sugarcane suppliers stratified according to the production area, as well as to evaluate their competitiveness, considering the variables productivity (PROD), total recovered sugar (TRS), average sugarcane cuts (ASC) and average total cost (ATC). For this, 55 sugarcane suppliers were selected to answer a survey, previously validated by specialists. These suppliers were stratified according to their respective production areas; the groups of small, medium, and large suppliers were examined through descriptive analysis and evaluated using the competitiveness index (CI) which investigated the variables (separately and jointly): PROD, TRS, ASC, and ATC, with equal weights. The results show that there is great variability within the different groups. Large suppliers stood out in the CI referring to PROD, while most small suppliers had the lowest CI in the variables PROD, ART, and ATC. When the variables were analyzed together, no group was able to reach the proposed high competitiveness index.
Keywords: Production costs; Productivity; Sugar energy